Pseudoprogression in patients with glioblastoma: clinical relevance despite low incidence - Radbruch, Alexander (Neuro Oncol, 2015)
BACKGROUND: According to the Response Assessment in Neuro-Oncology criteria, new enhancement within the radiation field on contrast enhanced T1-weighted images within 12 weeks after completion of radiotherapy should not qualify for progressive disease, since up to 50% of these cases may be pseudoprogression (PsP). To validate this concept, we assessed incidence and overall survival (OS) of patients with suspected and confirmed PsP dependent on different time intervals and definitions of PsP. METHODS: Patients with newly diagnosed glioblastoma and an enhancement increase of at least 25% after completion of standard radiochemotherapy at month 1, 4, 7, or 10 were eligible. Based on the development of the enhancement in follow-up examinations, patients were categorized as either PsP (subgrouped as complete resolution/decrease >50% and decrease <50%/stable) or true progression. RESULTS: Out of 548 patients, 79 fulfilled the inclusion criteria. Of these 79 patients, 9 (11.4%) showed PsP (6/45 patients at 1 month, 2/17 at 4 months, 1/9 at 7 months, and 0/8 at 10 months). Complete resolution of the enhancement was found in 1, decrease >50% in 3, decrease <50% in 2, and stable enhancement in 3 patients with PsP. Patients with PsP showed a significantly longer OS (P < .012). No difference in OS was found among PsP subgroups. CONCLUSIONS: This series challenges the current concept of PsP. Even though we could confirm a prolonged OS of patients with PsP, the incidence of PsP was lower than reported previously and extended beyond 12 weeks.